Pengaruh Penggunaan Faktor-Faktor Produksi Terhadap Produksi Usahatani Apel - Karimah, Mufidatul; Hidayati, Novi Itsna (Agrotechbiz : Jurnal Ilmiah Pertanian, 2024)
Agriculture can be interpreted as an asset by carrying out organizational or management activities and agricultural activities. Agricultural activities also regulate agricultural production facilities and technology in businesses related to agriculture. Likewise, farming refers to commercial or business activities that involve managing land, plants, animals. , or other agricultural resources with the aim of producing agricultural products for sale and purchase. This includes various activities such as protection, maintenance, harvesting, and marketing of agricultural products. The aim of this research is to analyze production costs in apple farming and to analyze the influence of factors production for apple farming, in this research using the R/C Ratio analysis method and for production factors using multiple linear regression (Cobb-Douglas) with the SPSS application. The determination uses a simple random sampling method, which involves taking samples randomly from the entire population with the same probability for each individual. The number of farmers we can take is 33 farmers. The results of this research are analysis of farming income by calculating the R/C ratio of 2.333. So, every additional Rp. 1 will increase revenue by Rp. 2,333,-. The factor that influences apple farming is land area because the significant value is less than 0.5. Farmers' suggestions are expected to further optimize the costs incurred in the use of production factors so that there is no waste of costs. Keywords: agriculture, farming, costs, apples, production factors.